Application Software For Learning CPU Process of Interrupt and I/O Operation - Fransiscus Ati Halim (IJNMT (International Journal of New Media Technology), 2017)
The purpose of this research is to have simulation software capable of processing interrupt instruction and I/O operation that in the future it can contribute in developing a kernel. Interrupt and I/O operation are necessary in the development of the kernel system. Kernel is a medium for hardware and software to communicate. However, Not many application software which helps the learner to understand interrupt process. In managing the hardware, there are times when some kind of condition exist in the system that needs attention of processor or in this case kernel which managing the hardware. In response to that condition, the system will issue an interrupt request to sort that condition. As the I/O operation is needed since a computer system not just consists of CPU and memory only but also other device such as I/O device. This paper elaborates the application software for learning Interrupt application. With interrupt instruction and I/O operation in the simulation program, the program will be more represent the process happened in the real life computer. In this case, the program is able to run the interrupt instruction, I/O operation and other changes are running as expected. Refers to its main purpose, perhaps this simulation can lead to developing the kernel in operating system. From the results of instruction’s testing above, has a result that shows that 90% of instructions are run properly. In executing instructions, simulation program still has a bug following after the execution of Jump and conditional Jump. Index Terms—Interrupt; I/O; Kernel; Operating System REFERENCES [1] C. Hamacher, Z. Vranesic, S. Zaky. Naraig Manjikian , Computer Organization and Embedded Systems 6th Edition; McGraw-Hill, 2012 [2] B. Brey. The Intel Microprocessors , Architecture, Programming, and Interfacing , 8th Edition. Pearson, 2008 [3] W.Stallings. Computer Organization and Architecture, 9th Edition Pearson , 2012 [4] F.A.Halim , Sutrisno, “Fundamental Characteristic of Central Processing Unit Simulation as a Basic Stage of Making Kernel”, Publish in Konferensi Nasional Sistem & Informatika (KNS&I 2010), 12-13 Nov 2010, Bali [5] Intel, IA-32 Intel® Architecture Software Developer’s Manual Volume 3: System Programming Guide, Denver: Intel Corporation, 2004 [6] Intel,IA-32 Intel 80386 Reference Programmer's,: I/O Instruction , https://pdos.csail.mit. edu/6.828/2014/readings/i386/s08_02.htm, available 17 June 2017